Chemoproteomic Approach to Explore the Target Profile of GPCR ligands: Application to 5‐HT1A and 5‐HT6 Receptors. Issue 4 (12th November 2015) - Gamo, Ana M.; González‐Vera, Juan A.; Rueda‐Zubiaurre, Ainoa; Alonso, Dulce; Vázquez‐Villa, Henar; Martín‐Couce, Lidia; Palomares, Óscar; López, Juan A.; Martín‐Fontecha, Mar; Benhamú, Bellinda; López‐Rodríguez, María L.; Ortega‐Gutiérrez, Silvia
Abstract: Determination of the targets of a compound remains an essential aspect in drug discovery. A complete understanding of all binding interactions is critical to recognize in advance both therapeutic effects and undesired consequences. However, the complete polypharmacology of many drugs currently in clinical development is still unknown, especially in the case of G protein‐coupled receptor (GPCR) ligands. In this work we have developed a chemoproteomic platform based on the use of chemical probes to explore the target profile of a compound in biological systems. As proof of concept, this methodology has been applied to selected ligands of the therapeutically relevant serotonin 5‐HT1A and 5‐HT6 receptors, and we have identified and validated some of their off‐targets. This approach could be extended to other drugs of interest to study the targeted proteome in disease‐relevant systems. Abstract : Target profile : Determination of the targets of a compound remains an essential aspect in drug discovery. Probes based on 5‐HT1A and 5‐HT6 serotonin receptor ligands reveal additional sites of action of these compounds (see figure).